2019
DOI: 10.1111/eje.12461
|View full text |Cite
|
Sign up to set email alerts
|

The availability of open‐access videos offered by dental schools

Abstract: Background The Internet has become an established learning tool in dental education where students can access online videos on a range of dental subjects. However, finding reliable peer‐reviewed content is not straightforward. Aim To evaluate the video content offered by UK and Republic of Ireland (RoI) Dental Schools on their YouTube channels and public websites. Methods Free videos offered on UK and RoI Dental schools websites and YouTube channels were watched and set according to its purpose, as educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 22 publications
0
24
0
2
Order By: Relevance
“…This observation resonates with other authors of previous studies who concluded that creating effective, innovative, and educational online content is a challenging and time-consuming exercise that will require a necessary transitional period of training and adaptation. 32,33 We recommend that this pressing student concern is addressed in time as teachers can be encouraged to enroll into online training courses and programs, which will give them the necessary tools needed to become acquainted with different aspects of virtual learning modalities. This will aid the dental educators in improving the quality of online sessions currently being delivered.…”
Section: Discussionmentioning
confidence: 99%
“…This observation resonates with other authors of previous studies who concluded that creating effective, innovative, and educational online content is a challenging and time-consuming exercise that will require a necessary transitional period of training and adaptation. 32,33 We recommend that this pressing student concern is addressed in time as teachers can be encouraged to enroll into online training courses and programs, which will give them the necessary tools needed to become acquainted with different aspects of virtual learning modalities. This will aid the dental educators in improving the quality of online sessions currently being delivered.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies published in scientific journals concerning the use of videos in dental education focus on the offering of teacher‐created videos to their own students, under very specific and controlled situations 26–29 . As a result, online dental content is delivered by unreliable sources 9 . Understanding how students use online dental educational videos during self‐learning sessions, out of the dental school, will be a major asset in integrating this behaviour into future methodological approaches.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Online content can be created and published by anyone without any peer reviews. 8,9 Infodemic is the term used by the World Health Organization to define the far-reaching, spreading overabundance of information, including false or misleading materials, that makes it hard for people to find reliable online content. 10,11 The scientific judgement of an undergraduate student may not be able to critically review online content sensibly.…”
Section: Introductionmentioning
confidence: 99%
“…O conteúdo que é disponibilizado nesse cenário digital é considerado bastante atrativo para os acadêmicos de odontologia, pois esses ensinamentos podem ser encontrados de diferentes formas, e o aluno pode selecionar aquela que melhor se adapta à necessidade do momento e ao seu estilo de aprendizagem. Além disso, é válido salientar que as redes sociais virtuais têm ganhado cada vez mais espaço na sociedade, o que corrobora para que o número de adeptos a esse sistema seja cada vez maior (Silva, Pereira & Walmsley, 2019;Turban et al, 2018).…”
Section: Introductionunclassified